Association between thyroid hormone levels with insulin resistance in obese euthyroid women with metabolic syndrome in Saudi Arabia: A cross-sectional study - Bin Obead, Manal; Al Badr, Nawal Abdullah; AlSedairy, Sahar Abdulaziz; Albrahim, Tarfa Ibrahim; Alhussain, Maha Hussain; Aljurbua, Tahani Ali; Arzoo, Shaista; Alqahtani, Weedad Saeed (Progress in Nutrition, 2021)
Background: The obesity epidemic is a pressing global health concern, as obesity rates continue to rise worldwide. This study examines the relationship between thyroid hormone levels, insulin resistance and components of metabolic syndrome in euthyroid’s. Methods: A pre-structured and pre-tested questionnaire was used to gather information and biochemical tests were performed using kits. The homeostatic model assessment (HOMA) ratio formula was used to quantify IR.Results: A total 100 obese women were clinically evaluated, from which 72 women were diagnosed with metabolic syndrome (MetS+). Body mass index (BMI), systolic blood pressure, total cholesterol (TC), triglyceride (TG), high-density lipoprotein (HDL-C) and thyroid-stimulating hormone (TSH) were statistically higher in MetS+ group. Even in euthyroids, TSH was positively associated with waist circumference and TC. TSH was also positively associated with HOMA-IR (r= 0.018*). FT4 was negatively associated with TC (r = -0.007*), LDL-C (r=-0.084*) and HOMA-IR value (r= -0.187**). The difference between two levels within normal range of TSH (TSH 2.7 resistant, < 2.7 sensitive) BMI, WC, TC, TG, LDL-C and TSH was higher in resistant group.Conclusion: Obese euthyroids exhibited a significantly positive correlation between HOMA IR values and TSH levels and significantly negative correlation between low normal FT4 and HOMA IR. It has also been established that thyroid function and lipid levels are related even in subjects classified as being euthyroid.